Ophthalmological Aspects of Mustard Gas Poisoning (focus on management) - Mehrdad Rafati-Rahimzadeh; Mehravar Rafati-Rahimzadeh; Sohrab kazemi; Seyedeh Roghieh Jafarian Amiri; Abbas Soleymani; Ali Akbar Moghadamnia (Caspian Journal of Internal Medicine, 2022)
Background: Amongst the chemical warfare agents, blistering (vesicant) agents can be significant materials. The most important agent in this group is sulfur mustard (mustard gas) which is known as “King of chemical warfare (CW) agents “. Exposure to this agent, seriously causes damages in several organs, such as the eyes. This article reviews the ophthalmological aspects of sulfur mustard with reference of its management. Methods: A wide-ranging search in PubMed databases, Thomson Reuters and Scopus was done and different aspects of chemical properties of sulfur mustard, its mechanism of action and effects on eyes, clinical finding, diagnostic evaluation, initiate actions, pharmaceutical and surgical interventions was reported. Results: Sulfur mustard can alkylate DNA and RNA strands and break down structures of protein and lipid of cell membrane. This may impair cell energy production, and leads to cell death. Exposure to sulfur mustard, therefore, causes such problems for organs, including irreversible damage to the eyes. Conclusion: Understanding the mechanism of the sulfur mustard effect and the early training in prevention injuries will cause fewer complications and damage to organs, including the eyes. Washing the eyes with tap water or eyewash solutions, using mydriatic drops, anti- inflammatory drugs, matrix metalloproteinase inhibitors and antibiotics may help to the management of poisoning. Surgical interventions including tarsorrhaphy, amniotic membrane transplantation, stem cell transplantation and corneal transplantation could reduce the harm to the victims.